The Wisdom of Healer for Low Back Pain Treatment in Ubon Ratchathani Province - Thiantongin, Pitchanan (Journal of Humanities and Social Sciences Loei Rajabhat University, 2023)
Low back pain, with a prevalence of approximately 70–85 percent worldwide, is a major public health and economic problem. This qualitative research study aims to collect wisdom about the treatment process for low back pain by folk healers in UbonRatchathani Province and investigate the pharmacological effects of herbal medicines by conducting in-depth interviews, 5 indigenous healers who are members of the indigenous healer’s club Observing and examining data from academic databases. The results of the research revealed that all indigenous healers inherited their knowledge from their ancestors and sought additional knowledge. There is a treatment process starting from 1) Relaxing muscles 2) Pressing massage 3) Scratching or kicking lines 4) Stretching the muscles after massage; and 5) use of herbal medicine. from examining the pharmacological effects of herbs It was found that most of them had anti-inflammatory effects such as Salacia chinensis L., Suregada multiflora (A.Juss.) Baill และ Derris scandens (Roxb.) Benth). Study and collect all the information about folk healers. shows that folk healers have knowledge. Wisdom that can take care of or alleviate the illnesses of people in the community However, the effectiveness of massage and herbal medicine should be studied further.